DETECÇÃO DE CRYPTOSPORIDIUM SP E GIARDIA SP EM MANANCIAIS E ÁGUAS DE ABASTECIMENTO PÚBLICO: MÉTODOS US-EPA 1623 E ELISA - Stancarki, Regina Célia Arantes; Correia, Marlene (Revista do Instituto Adolfo Lutz, 2006)
Ver PDF.